THE ARABIC LANGUAGE BETWEEN COGNITIVE STUDIES AND INTERDISCIPLINARY RESEARCH - Al-Omarini, Mohammed bin Abdul-Azeez; Al-Nauimi, Afrah Saleh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
"Interdisciplinarity" has become an unavoidable aspect of cognition, as various fields of knowledge have emerged from the blending of numerous sciences and diverse methodologies. In ancient times, interdisciplinarity was a recognized cultural phenomenon, evident to anyone familiar with the biographies of writers and scholars such as Ibn Sina (who died in 427 AH), who integrated medicine, philosophy, literature, and music. The concept of encyclopedic knowledge is prevalent, representing a different perspective that contrasts with the ideal of strict disciplines and the fragmentation of isolated intellectual domains created by interdisciplinary studies, where texts were systematically confined within rigid structures. This new cognitive approach emerged in the latter half of the 20th century due to the information explosion and shifts in scientific and cultural knowledge across various societies. These changes compelled modern scientific research to move toward transdisciplinary studies, which can address complex issues that single-discipline efforts alone cannot resolve. Instead, they require collaboration among multiple scientific fields to broaden perspectives and achieve higher quality outcomes through their interactions. Connecting language to fields such as philosophy, psychology, sociology, anthropology, music, and various arts—along with integrating critical approaches from related disciplines like new rhetoric, stylistics, pragmatics, and discourse analysis—has created an unprecedented interdisciplinary synergy. This collaboration involves perceptive cognitive sciences, cognitive psychology, and neuroscience, aiming to delve into the complexities of human linguistic comprehension and perception. By leveraging advancements in scientific fields, technology, neurology, and psychology, this approach seeks to understand the nature of linguistic communication, uncover the foundations of human understanding, and unravel the mysteries of memory, among other linguistic functions.